Democratic Innovations: Reinforcing or Changing Perceptions of Trust?. Issue 7 (7th June 2017) - Åström, Joachim; Jonsson, Magnus E.; Karlsson, Martin
ABSTRACT: Declining trust in representative institutions is considered one of the most significant political problems of our time. It is often suggested that democratic innovations—or mechanisms which aim to increase and deepen citizen participation in the political decision-making process—can help reverse this trend. However, empirical research about actual effects of participation on trust is scarce, and weakened by causality problems. With survey data representing 1, 470 participants in a landmark Swedish e-petition system, the article shows that both generalized attitudes and process evaluations matter in how trust is affected by democratic innovations.